2014
DOI: 10.1002/cmdc.201300420
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of 4‐Amino‐N‐(4‐aminophenyl)benzamide Analogues of Quinoline‐Based SGI‐1027 as Inhibitors of DNA Methylation

Abstract: Quinoline derivative SGI-1027 (N-(4-(2-amino-6-methylpyrimidin-4-ylamino)phenyl)-4-(quinolin-4-ylamino)benzamide) was first described in 2009 as a potent inhibitor of DNA methyltransferase (DNMT) 1, 3A and 3B. Based on molecular modeling studies, performed using the crystal structure of Haemophilus haemolyticus cytosine-5 DNA methyltransferase (MHhaI C5 DNMT), which suggested that the quinoline and the aminopyridimine moieties of SGI-1027 are important for interaction with the substrates and protein, we design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Interestingly, the negative effect of adding acetyl groups on DNMT3 inhibition is milder than that of adding methoxy groups, given that compounds 11 and 12 still showed some degree of inhibition on both DNMT3A and DNMT3B enzymes (IC 50 ’s in the 100–215 μM range; Table 1). The observation that methoxy groups reduce DNMT inhibition seems to be in agreement with a recent report by Rilova et al, in which they reported that dimethoxytriazine groups decreased the DNMT3A inhibitory activity of quinolone-based DNMT inhibitors (58). …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the negative effect of adding acetyl groups on DNMT3 inhibition is milder than that of adding methoxy groups, given that compounds 11 and 12 still showed some degree of inhibition on both DNMT3A and DNMT3B enzymes (IC 50 ’s in the 100–215 μM range; Table 1). The observation that methoxy groups reduce DNMT inhibition seems to be in agreement with a recent report by Rilova et al, in which they reported that dimethoxytriazine groups decreased the DNMT3A inhibitory activity of quinolone-based DNMT inhibitors (58). …”
Section: Resultssupporting
confidence: 92%
“…Nevertheless, recent developments with small molecule inhibitors have showed that in vitro DNMT3A inhibition is possible without the presence of carboxylate groups (58). Thus, results of this work showed that compounds bearing either a free carboxylic acid (9), or a carboxylate methyl ester (10), exerted a better inhibitory profile than resveratrol against both DNMT3 enzymes (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, two of them, azacitidine and decitabine, have been approved by FDA (Food and Drug Administration) for the treatment of myelodysplastic syndromes [25,26]. Moreover, non-nucleoside DNMTis, such as RG-108 [27], which was identified via virtual screening methods; and SGI-1027, a quinoline derivative, have been proposed as DNMTis [28,29]. However, the weak inhibitory activity of these compounds [30] indicates a need for the search of more effective inhibitors in the future.…”
Section: Figure 1 May Go Herementioning
confidence: 99%
“…Consequently, derivatives ( 16 ) and ( 17 ) also showed a DNA-competitive inhibition of DNMT. Compound ( 16 ) is the most potent DNMT1 inhibitor among them [4,42,43]. …”
Section: Inhibition Of Dna Methylationmentioning
confidence: 99%